The Relationship Between Impulsivity and Problematic Internet Use Mediated by Boredom Proneness in Adolescents - Oliveira, Mariana; Fernandes, Lucas; Gruber, Lukas (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the relationship between impulsivity and problematic internet use in adolescents, with boredom proneness as a mediating variable. Methods and Materials: A descriptive correlational design was employed, involving 450 Brazilian adolescents aged 13 to 18 years, selected using multistage cluster sampling. Data were collected through the Barratt Impulsiveness Scale – Version 11 (BIS-11), the Boredom Proneness Scale (BPS), and Young’s Internet Addiction Test (IAT). Statistical analyses included Pearson correlation to examine bivariate associations, and Structural Equation Modeling (SEM) with maximum likelihood estimation in AMOS 21 to test the hypothesized mediation model. Model fit was assessed using χ², χ²/df, GFI, AGFI, CFI, RMSEA, and TLI indices. Findings: Pearson correlation analyses revealed significant positive associations between impulsivity and boredom proneness (r = .48, p < .001), impulsivity and problematic internet use (r = .42, p < .001), and boredom proneness and problematic internet use (r = .53, p < .001). The SEM analysis indicated a good model fit (χ²/df = 2.04, GFI = 0.95, AGFI = 0.93, CFI = 0.97, RMSEA = 0.048, TLI = 0.96). Impulsivity significantly predicted boredom proneness (β = 0.48, p < .001) and problematic internet use both directly (β = 0.22, p < .001) and indirectly through boredom proneness (β = 0.22, p < .001), with the total effect being substantial (β = 0.44, p < .001). These findings confirm partial mediation, indicating that boredom proneness explains a significant portion of the link between impulsivity and problematic internet use. Conclusion: The results highlight boredom proneness as a key mechanism linking impulsivity to problematic internet use among adolescents. Interventions aiming to reduce excessive internet use in this population should address both impulsive tendencies and the ability to tolerate boredom, fostering adaptive coping strategies in low-stimulation contexts.